Abnormal psychology: new research - Friedman, Helen D.; Revera, Paulina K. (Nova Science Publishers, 2009)
Short communication rumination and avoidance in depression : the relationship between rumination, avoidance and depression in depressed inpatient / Filip Raes, Heleen Vandromme, and Dirk Hermans -- The spectrum and self-harm in adolescence and young adulthood : moving toward an integrative model of pathogenic mechanisms / Christa D. Labouliere and Marc S. Karver -- Modeling of dyslexia : is a unitary model of dyslexia possible? / Timothy C. Papadopoulos, George K. Georgiou, Sotirios Douklias -- Overgeneral attachment memory : overgeneral attachment-related autobiographical memory in children / Jessica L. Borelli ... [et al.] -- Depression and a parenting intervention : can caregiver depression bring a good parenting intervention down? : the case of parent-child interaction therapy / Mark Scholes, Melanie J. Zimmer-Gembeck, and Rae Thomas -- The role of negative affective alence in return of fear / Inneke Kerkhof ... [et al.] -- The neuropsychology of alcoholism / J. Uekermann and I. Daum -- Perception without awareness : the qualitative differences approach / Juan J. Ortells ... [et al.] -- Intraphychic factors contributing to adolescent depression / Lisa C. Milne and Philip Greenway -- A hermeneutic approach to culture and psychotherapy / John Chambers, Gary Foster, and Susan James